Disk scheduling using a customized discrete firefly algorithm - Amandeep Singh; Sidharth Thapar; Abhishek Bhatia; Saurabh Singh; Rinkaj Goyal (Cogent Engineering, 2015)
This study empirically investigates the usage of a customized discrete firefly algorithm (DFA) for ordering the disk requests to minimize the total access time. The procedure simulates the movement of each firefly within a population towards others using a variation of edge-based mutation. The algorithm was applied to randomized standard disk sequences with varying length of input disk requests. Owing to the greater impact of seek time in the determination of access time for a disk having sizable number of tracks, this has been taken as the primary performance factor in the scheduling of tasks. The analysis of the results obtained establishes the relative advantage of using the firefly optimization method over the traditional disk scheduling algorithms.